Reference to Mazhab in fatwa deliberation: analysis on the administration of Islamic law in Malaysia - Hussain, Mohammad Azam; Megat Latif, Hairuddin; Md Nor, Mohd Zakhiri; Md Desa, Md Rejab; Mohd Khalid, Al-Hanisham; Mohd Akhir, Muhammad Azri (Global Academic Excellence, 2018)
The four major sects recognized in Islam in understanding the Syariah law are the Hanafi, Maliki, Syafie and Hanbali. In Malaysia, Article 3 of the Federal Constitution stipulates that Islam is the Religion of the Federation without elaborating further on sectarian aspect that needs to be followed by Muslims in the country. For the majority of Muslims in Malaysia, Shafie sect is a reference and guidance in their daily practice. The question arises, what is the legal position regarding reference to the sect in the fatwa deliberation in the states of Malaysia. By using content analysis method, this article examines the provisions of laws in the states of Malaysia in regulating the fatwa affairs. This study found that, the majority of laws regulating fatwa affairs in the states of Malaysia have stipulated that the reference to the accepted view (qaul muktamad) of the Syafie sect is a priority in the Syariah deliberation. However, if that accepted view (qaul muktamad) is contrary to the public interest, then the reference to the accepted view (qaul muktamad) of the Hanafi, Maliki or Hanbali sects can be used as a reference. The study also found that only the state of Perlis, which provides a reference to the al-Quran and al-Sunnah in the fatwa deliberation by the State Fatwa Committee.